Elliptic Curves, Modular Forms and Iwasawa Theory In Honour of John H. Coates' 70th Birthday, Cambridge, UK, March 2015 - Loeffler, David; Zerbes, Sarah Livia (Springer Proceedings in Mathematics & Statistics, 2016)
Celebrating one of the leading figures in contemporary number theory - John H. Coates - on the occasion of his 70th birthday, this collection of contributions covers a range of topics in number theory, concentrating on the arithmetic of elliptic curves, modular forms, and Galois representations. Several of the contributions in this volume were presented at the conference Elliptic Curves, Modular Forms and Iwasawa Theory, held in honour of the 70th birthday of John Coates in Cambridge, March 25-27, 2015. The main unifying theme is Iwasawa theory, a field that John Coates himself has done much to create. This collection is indispensable reading for researchers in Iwasawa theory, and is interesting and valuable for those in many related fields. .